The Impact of Mobile Legends Games on Student Learning Motivation: The Role of Parents and Teachers - Sri Rochmayanti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The advancement of technology is accelerating. Beginning with telecommunicationstechnology, the internet, and intelligent computer-based technology. Until the first cellphones were used to fulfill communication needs, cellphones could only be used to do a fewthings, such as easily finding any information all over the world, playing online gamesfrom anywhere, and so on. Mobile Legends games are extremely popular. Not only doteenage boys enjoy playing these online games, but so do many girls. The goal of this studywas to determine the impact of Mobile Legends game addiction on students' learningmotivation, as well as the role of parents and teachers. This is a type of library research.The data used in the study was analyzed using data reduction, data display, and drawingconclusions. Reading and recording important information contained in various journalsrelated to the research being conducted are data collection techniques. It is expected thatthe results of this study can be used as insights, references, and basic and considerationfor future researchers in order to become other research areas whose topics are relevant tothis study.